2019
DOI: 10.1002/app.48744
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and mechanical properties of cellulose/LDPE composites using sustainable and fully renewable compatibilisers

Abstract: Cellulose composites with polyethylene (PE) permit to reinforce this commodity polymer, while at the same time introducing renewable content and thus minimizing the use of petroleum‐based feedstocks. Herein, we report on two fully renewably sourced and sustainably synthesized compatibilisers based on amylose and starch, which allow for such cellulose dispersion in low‐density PE (LDPE). These compatibilisers advantageously combine the hydrophilicity of carbohydrates with the hydrophobicity of fatty acids. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…High-density polyethylene (HDPE) was supplied by Unipetrol RPA, Czech-Republic. This HDPE is commercially used in the extruded pipes application, and it has a melt flow rate (190/5) of 0.4 g/10 min, M w of 185,000 g/mol, a polydispersity of 11, and a density of 0.952 g/cm 3 , according to the supplier specifications. Talc powder supplied by Bassermann, Germany was used as filler.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-density polyethylene (HDPE) was supplied by Unipetrol RPA, Czech-Republic. This HDPE is commercially used in the extruded pipes application, and it has a melt flow rate (190/5) of 0.4 g/10 min, M w of 185,000 g/mol, a polydispersity of 11, and a density of 0.952 g/cm 3 , according to the supplier specifications. Talc powder supplied by Bassermann, Germany was used as filler.…”
Section: Methodsmentioning
confidence: 99%
“…Post-polymerization modification results in polymer materials with an interesting range of properties and characteristics, such as enhanced mechanical properties, improved electrical conductivity, and better heat transfer properties [1,2]. Most properties of the polymers can be enhanced using various reinforcing fibers, cellulose, particulates, and fillers to meet material requirements in a wide range of applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, progress has been made by Meier, who introduced a more sustainable process for esterification of cellulose in a switchable 1,8diazabicyclo[5.4.0]undec-7-en (DBU)/CO 2 solvent system that holds promise for the development and processing of advanced cellulose-based plastics. [165][166][167][168][169][170][171][172][173] Tough and transparent cellulose nanopaper with high porosity was derived from aqueous dispersions of cellulose nanofibrils. [174][175][176][177][178][179] Advances in nanofibrillated cellulose production and its potential applications, ranging from nanopaper to nanocomposites, coatings, and food packaging, have been addressed by several reviews.…”
Section: Bio-based Plastics Extracted From Naturementioning
confidence: 99%
“…The young's modulus is directly proportional to fibers content. [51][52][53] The flexural test showed that the properties increased when the addition of fibers increased in the LDPE. In general, flexural strength increases with an increase in F I G U R E 4 SEM of MN with a zoom of (a) 300×; (b) 500×; and OM of MN-based LDPE composites (5, 10, and 20 wt/wt%) with a zoom of (c, e, g) 100× and 200× (d, f, h fiber loading, explaining that fiber addition makes the composite more ductile.…”
Section: Mechanical Propertiesmentioning
confidence: 99%